Nursing and Midwifery Students\' Emotional Intelligence and its Relationship with some Demographic Characteristics, Golestan University of Medical Sciences - Zahra Sabzi; Hamideh Mancheri; Zahra Royani; Seyedyaghoob Jafari; Mahnaz Modanloo (Golestan University of Medical Sciences, 2015)
Background and Objective: Nursing students are experiencing stress in related to academic and clinical training programs.  Given the importance of promoting mental health and emotional intelligence in academic performance,  the study of emotional intelligence and related factors could be the basis for strengthening this important variable by designing and implementing of effective training programs. Material and Methods: This cross-sectional study was conducted on 125 nursing & midwifery students selected randomly in 2013. The instruments were a demographic checklist and Shyryng Sybrya Emotional Intelligence Questionnaire. The data was analyzed in SPSS16 using descriptive statistics (mean and standard deviation) and ANOVA, T- TEST (p&le 0.05). Results: The mean of emotional intelligence was 109.12±12.27 in nursing and 113.32±13.26 in midwifery students.  The  total score and  the score of all dimensions of  Emotional Intelligence Questionnaire were not related significantly with some demographic factors such as age, residential place, interest to major and economic status (P>0.05), in both nursing and midwifery students. In nursing students, the meaningful relation was found just between Self-awareness dimension and gender (P=0.034) and grade point average (GPA)   (P=0.049). The score of Self-awareness was higher in female students and  in the students with higher GPA. Conclusion: Regarding the relationship between some demographics and emotional intelligence, we can design and implement effective educational programs to boost this important component.